Efektivitas Ekstrakulikuler Bahasa Arab dalam Meningkatkan Maharah Al-Kalam Siswa Kelas II MTs di Pondok Pesantren Husnayain Salulebbo Mamuju Tengah - Muh Ichsan; Abdul Qahar Zainal; St. Johariyah; Andi Hasriani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to reveal the effectiveness of Arabic extracurricular activities, specifically muhadharah and muhadatsah, as well as the daily Arabic language program in improving maharah al-kalam of second-grade students of MTs Husnayain Salulebbo. Maharah al-kalam or the ability to speak Arabic is an important competency that needs to be developed at the secondary education level, especially in madrasahs. This study used a descriptive qualitative method to collect and analyze data through interviews, observations, and documentation. The results showed that muhadharah, muhadatsah, and the daily Arabic language program were effective in improving students' maharah al-kalam. Muhadharah activities were implemented through group formation, lecture text creation, and regular evaluations, which helped students develop their speaking skills. Meanwhile, muhadatsah activities were carried out through interactive dialogue, a communicative approach, and regular supervision that encouraged students to be more active in communicating in Arabic. The daily Arabic language program, which involved providing mufrodat (new vocabulary), adaptation to daily situations, and continuous evaluation, also proved effective. Supporting factors for the success of this activity include routine activities, sanctions for violators, and competitions that increase student motivation. However, there are several inhibiting factors, such as a lack of student interest and seriousness in participating in the activity, as well as external factors such as limited facilities and infrastructure, and bad weather that can disrupt the implementation of the activity. This study concludes that extracurricular Arabic language activities can effectively improve students' maharah al-kalam if supported by appropriate methods and strategies, and the presence of adequate supporting factors.